2009
DOI: 10.2319/060408-293.1
|View full text |Cite
|
Sign up to set email alerts
|

TMD in Consecutive Patients Referred for Orthognathic Surgery

Abstract: Objective: To answer the question whether temporomandibular disorders (TMD) were more common in a group of individuals referred for orthognathic surgery than in a control group. The null hypothesis was that neither the frequency of signs and symptoms of TMD or diagnosed TMD would differ between the patient group and a control group. Materials and Methods: A sample of 121 consecutive patients referred for orthognathic surgery at the Department of Oral Maxillofacial Surgery, Malmö University Hospital, Sweden, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 22 publications
3
32
2
4
Order By: Relevance
“…The statistical difference observed in the comparison of AQ scores between GDFD and CG agrees with the results of some studies that indicated predominance of signs and symptoms of TMD in individuals with DFD during presurgical orthodontic treatment compared to the control group (1,11,12) . It should be highlighted that no study has employed the anamnesis questionnaire used in this study, yet included clinical examination of the TMJ, visual analogue scale, anamnesis index and of dysfunction of Helkimo (21) , or applied the RDC/TMD protocol (22) .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The statistical difference observed in the comparison of AQ scores between GDFD and CG agrees with the results of some studies that indicated predominance of signs and symptoms of TMD in individuals with DFD during presurgical orthodontic treatment compared to the control group (1,11,12) . It should be highlighted that no study has employed the anamnesis questionnaire used in this study, yet included clinical examination of the TMJ, visual analogue scale, anamnesis index and of dysfunction of Helkimo (21) , or applied the RDC/TMD protocol (22) .…”
Section: Discussionsupporting
confidence: 79%
“…The dento-occlusal imbalance may be associated with temporomandibular dysfunction (TMD) (7,8) , which corresponds to the generic term to a clinical range of signs and symptoms involving the masticatory muscles, the joint itself and associated structures (9) . Different authors observed predominance of signs and symptoms of TMD in individuals with DFD during presurgical orthodontic treatment compared to a control group (10,11,12) . The literature demonstrates reduced bite force values in individuals with DFD during presurgical orthodontic treatment, compared to a control group with normal occlusion and absence of signs and symptoms of TMD (5,13,14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…The differences in relation to the present study may be justified by the fact that, in the study by Abrahamsson et al 29 , despite the larger sample, the control group was not matched by gender and age. The prevalence of articular diagnoses (GII and GIII) in subjects with DFD, in this study, can be attributed to the skeletal and dental imbalance in these individuals, which is not present in the controls, since internal changes in the TMJs of…”
contrasting
confidence: 45%
“…The importance of occlusion and its relationship between the cause or maintenance of TMD cases, compared with other factors, specifically in individuals presented with DFD, has been widely discussed in the literature 15,[27][28][29] . The present study found that 97% of subjects with DFD showed some degree of TMD, while in the CG, the percentage of this disorder was 33%, which may be linked to the fact that TMD symptoms such as pain, are often the main complaint of patients presented with malocclusion 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation